A pedagogical meeting place or a problem space? Extending play-based pedagogy in Year One. Issue 2 (17th February 2022) - Nicholson, Philip; Hendry, Helen
ABSTRACT: School readiness performance measures, such as the Good Level of Development (GLD), are increasingly associated with children's readiness to start formal learning, presenting challenges for supporting the transition to compulsory school. This research focuses on how an English primary school extended play-based pedagogy into Year One for children who did not achieve a GLD. Over a period of six-months, regular observations and interviews with senior leaders and teachers were carried out. The data cautions against an over-reliance on the GLD and identifies a number of challenges associated with extending play-based pedagogy into Year One when it is positioned as an intervention.